Aryl hydrocarbon receptor mediates the cardiac developmental toxicity of EOM from PM2.5 in P19 embryonic carcinoma cells. (February 2019) - Chen, Tao; Jin, Hongmei; Wang, Huimin; Yao, Yugang; Aniagu, Stanley; Tong, Jian; Jiang, Yan
Abstract: Ambient fine particulate matter (PM2.5 ) has been found to be associated with congenital heart defects, but the molecular mechanisms remain to be elucidated. Our previous study revealed that extractable organic matter (EOM) from PM2.5 exerted cardiac developmental toxicity in zebrafish embryos. The aim of the current study is to explore the effects of EOM on cardiac differentiation of P19 mouse embryonic carcinoma stem cells. We found that EOM at 10 μg/ml (a non-cytotoxic dose level) significantly reduced the proportion of cardiac muscle troponin (cTnT) positive cells and the percentage of spontaneously beating embryoid bodies, indicating a severe inhibition of cardiac differentiation. Immunofluorescence and qPCR data demonstrated that EOM increased the expression levels of the aryl hydrocarbon receptor (AhR) and its target gene Cyp1A1 and diminished the expression level of β-catenin. Furthermore, EOM treatment significantly upregulated cell proliferation rate and elevated the percentage of γH2A.X positive cells without affecting apoptosis. It is worth noting that the EOM-induced changes in gene expression, cellular proliferation and DNA double strain breaks were attenuated by the AhR antagonist CH223191. In conclusion, our data indicate that AhR mediates the inhibitory effects of EOM (from PM2.5 ) on the cardiac differentiation of P19 cells. Graphical abstract: Highlights: EOM from PM2.5 collected in Suzhou contained nine of the sixteen EPA-priority PAHs. EOM heavily inhibited cardiomyocyte differentiation of P19 cells, which could be attenuated by AhR antagonist. The EOM-inhibited canonical Wnt signaling was mediated by AhR activation in P19 cells. EOM enhances γH2AX signals and cell proliferation, which could be abated by AhR antagonist.